Correlation between education, occupation, family income, and self confidence with exclusive breastfeeding - Ari Tuti Wahyuni; Lina handayani; Aprilia Rahmadani (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2016)
Background: The scope of exclusive breastfeeding in Puskesmas Pengasih II in Kulon Progo district of DI Yogyakarta, is still below national target (80%). Some factors that affect this problem are level of education, occupation, the mother’s self confidence, and the family’s economical income. This study aims to determine the correlation between education, occupation, family income, and mother’s self confidence with exclusive brestfeeding in Puskesmas Pengasih II. Objective: The objective of this study is to determine the correlation between education, occupation, family income, and mother’s self confidence with exclusive brestfeeding in Puskesmas Pengasih II. Method: This study is an observational study with cross sectional method and total sampling technique. The study population is all mothers who has 6 – 12 months old babies. Data analisis is done using chi square test with alpha = 5%. Results: There are statistically significant correlation between the mother’s occupation (p=0,036), family income (p=0,000) and self confidence (p=0,000) with exclusive breastfeeding in Puskesmas Pengasih II of Kulon Progo district. There are no statistically significant correlation between level of education (p=0,948) with exclusive breastfeeding in Puskesmas Pengasih II of Kulon Progo district. Conclusion: There are statistically significant correlation between the mother’s occupation, family income, and self confidence with exclusive breastfeeding in Puskesmas Pengasih II of Kulon Progo district. There are no statistically significant correlation between level of education with exclusive breastfeeding in Puskesmas Pengasih II of Kulon Progo district.